Estudio germinativo de Euterpe precatoria Mart. Huasaí en camas almacigueras aplicando diferentes tratamientos pre-germinativos, San Juan Bautista, Loreto-Perú - Leon Flores, Janet (2003)
The study was carried out at the facilities of the Puerto Almendra Forestry Research and Education Center of the National University of the Peruvian Amazon, located on the right bank of the Nanay River, 22 km south-west from the city of Iquitos, (3° 49' 40" LS y 73° 22'30" LO), at an approximate altitude of 122 msnm, belongs to the District of San Juan Bautista, Province of Maynas, Loreto Region (UNAP, 2019, p.1). The study was experimental, in random blocks with 06 treatments, and 03 repetitions, the following treatments were considered Y0 if treatment, Y1 soaking in H2O for 1 day, Y2 soaking in H2O for 2 days, Y3 soaking in H2O for 4 days, Y4 immersion in hot H2O 50ºC until cooling and Y5 partial uncovering of the integument, it was planted in the beds with irapay shed. Treatments Y4 and Y5 are the best treatments with 100% germination power, very good germination energy and viability. The inadequate application of pregermination treatments is a determining factor in the loss of viability of Euterpe precatoria, Mart .